Structural design of a stent for a percutaneous aortic heart valve - Esterhuyse, Anton (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.